35 “Ur” Type Anti-Tank Rifle – A Numerical Analysis of Armour Penetration of a World War II Tank - Mariusz MAGIER; Mariusz MAGIER (Karabin przeciwpancerny wz. 35 „Ur” – analiza numeryczna procesu penetracji opancerzenia czołgu z okresu II wojny światowej, 2019)
The paper presents a simulated process of penetration of a steel slab with a strength performance approximate to that of World War II battle tanks with a 7.92 mm DS projectile fired from the 35 “Ur” type anti-tank rifle. The basic technical parameters necessary for the simulation process were sourced from historical records. The FEM (Finite Element Method) applied in LS-Dyna enabled an estimation of the penetrating capability of the DS projectile. Decisive to the high penetrating capability of the DS projectiles were the non-optimized properties of armour steel (its high brittleness) and a high kinetic energy of the projectile, which generated high shearing stresses upon impact against the steel slab causing the effect of ‘plugging’ upon penetration. The numerical simulation results confirmed the high combat effectiveness of the DS projectile and the argument that the DS projectile could pierce a 20 mm thick armour plate made from the material applied during the World War II era.
Keywords: Balistyka końcowa- modelowanie wnikania pocisków w metalowe przegrody; Balistyka końcowa- modelowanie wnikania pocisków w metalowe przegrody